Using Homer’s Odyssey as a Culturally Familiar Literary Text in Foreign Language Teaching - Stylianou, Elina (International Journal of Language and Literary Studies, 2024)
There has been increasing interest among TESOL teachers in the use of literary text as a resource in language learning, because it enhances students’ language skills and educational potential. This case study explores students’ engagement with Homer’s Odyssey as a culturally familiar literary text in their learning of English as a foreign language, in a Cypriot secondary school context. As a teacher-researcher, I designed and delivered an intervention of nine sessions to three classes of twenty Year 2 students. Reader-response theory was used to explore students’ reactions to the literary text. This study provides a new context, secondary school setting; most of the previous empirical studies have been undertaken in university settings and have focused on reading comprehension. The present study focuses on students’ voices, through exploring their perceptions and their responses to the literary text. The findings revealed students’ positive engagement, through their active involvement in the sessions and their enjoyment of the classes. Students’ emotional engagement with the text made them enrich their vocabulary and engage in writing and speaking tasks. Cultural familiarity provides appropriate scaffolding for teachers to use literary text in EFL teaching; culturally familiar literary text can enhance language teaching when used as an additional material to EFL curriculum. This teaching approach can therefore serve as a guideline for language teachers and for curriculum enhancement purposes.